Peran Investasi Berkelanjutan Kebijakan Pemerintah Dan Keterlibatan Masyarakat Dalam Pencapaian SDGS - Uci Oktavia; Rista Intan Permatasari; Febrika Nurfianti; Nia Nur Yanti Agustin; Maria Yovita R. Pandin (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
Achieving the Sustainable Development Goals (SDGs) requires a holistic approach that integrates sustainable investment, government policy, and community engagement. Indonesia, as a country with significant resource potential and complex development challenges, faces pressure to accelerate SDG achievement in an inclusive and equitable manner. This study aims to thoroughly examine the contributions of these three elements in supporting the sustainable development agenda. Sustainable investment serves as a vital instrument by directing financing toward sectors that support the transition to a green economy, integrating environmental, social, and governance (ESG) principles. The government plays a central role through policies, regulations, and incentives-such as Presidential Regulation No. 112 of 2022 and OJK policies-designed to strengthen the green finance ecosystem. However, investment and policy alone will not be effective without active community involvement. Community participation in planning and monitoring development promotes accountability and strengthens a sense of ownership over development programs. This research uses a descriptive qualitative approach, utilizing secondary data collected through literature studies and field observations. Findings indicate that synergy among stakeholders is key to successful SDG implementation, especially at the local and village levels. Barriers such as limited outreach, low community participation, and resource constraints remain major challenges. Therefore, strengthening community capacity and cross-sector collaboration are essential to achieving sustainable development. The results of this study are expected to provide strategic input for policymakers and development practitioners in effectively integrating sustainability approaches.